Cancer-associated fibroblasts induce trastuzumab resistance in HER2 positive breast cancer cells. Issue 4 (4th February 2015) - Mao, Yan; Zhang, Yuzi; Qu, Qing; Zhao, Meizhong; Lou, Ying; Liu, Junjun; huang, Ou; Chen, Xiaosong; Wu, Jiayi; Shen, Kunwei
Abstract : CAFs isolated from HER2+ patients secreted higher levels of IL6 which expanded cancer stem cells and activated multiple pathways, then induced trastuzumab resistance in HER2 positive breast cancer cells. Abstract : Whether and how cancer-associated fibroblasts induce trastuzumab resistance in HER2+ breast cancer is still elusive. We analyzed the percentage of cancer stem cells and multiple pathway status before and after trastuzumab treatment in HER2 positive breast cancer cells co-cultured with conditional medium (CM) from CAFs. The results suggest that CAFs induce trastuzumab resistance by expanding cancer stem cells and activating multiple pathways, such as NF-κB, JAK/STAT3 and PI3K/AKT; combination of an anti-IL6 antibody, or multiple pathway inhibitors with trastuzumab in HER2 positive breast cancer maybe a novel strategy to reverse trastuzumab resistance.